2019
DOI: 10.1164/rccm.201807-1292oc
|View full text |Cite
|
Sign up to set email alerts
|

YES1 Drives Lung Cancer Growth and Progression and Predicts Sensitivity to Dasatinib

Abstract: Rationale: The characterization of new genetic alterations is essential to assign effective personalized therapies in non-small cell lung cancer (NSCLC). Furthermore, finding stratification biomarkers is essential for successful personalized therapies. Molecular alterations of YES1, a member of the SRC (proto-oncogene tyrosine-protein kinase Src) family kinases (SFKs), can be found in a significant subset of patients with lung cancer. Objectives: To evaluate YES1 (v-YES-1 Yamaguchi sarcoma viral oncogene homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…The characterization of new genetic alterations is essential to assign effective personalized therapies in NSCLC; furthermore, finding stratification biomarkers is essential for successful personalized therapies. In this direction, Garmendia et al showed that molecular alterations of Yes can be found in a significant subset of patients with lung cancer and they demonstrated an association between these alterations and prognosis using Yes status as predictive biomarker [76]. Also, the same authors demonstrated that stable Yes overexpression in human NSCLC cell lines induced proliferation, increased tumor growth and metastasis, but conversely, genetic depletion of Yes using siRNAs or CRISPR/Cas9 in human NSCLC cell lines reduced proliferation, survival, and invasion in vitro and tumor growth and lung metastatic growth.…”
Section: Lung Cancermentioning
confidence: 99%
“…The characterization of new genetic alterations is essential to assign effective personalized therapies in NSCLC; furthermore, finding stratification biomarkers is essential for successful personalized therapies. In this direction, Garmendia et al showed that molecular alterations of Yes can be found in a significant subset of patients with lung cancer and they demonstrated an association between these alterations and prognosis using Yes status as predictive biomarker [76]. Also, the same authors demonstrated that stable Yes overexpression in human NSCLC cell lines induced proliferation, increased tumor growth and metastasis, but conversely, genetic depletion of Yes using siRNAs or CRISPR/Cas9 in human NSCLC cell lines reduced proliferation, survival, and invasion in vitro and tumor growth and lung metastatic growth.…”
Section: Lung Cancermentioning
confidence: 99%
“…Other well-characterized oncogenes also present in the EPHA-ephrin signaling pathway include TIAM, YES1, and HRAS (Yang et al 2015;Dotto and Rustgi 2016;Garmendia et al 2019). MYH10, the only pathway member in our cohort with alterations in both single-nucleotide variation (SNV) and copy-number variation (CNV), has been identified as an important hub in other quantitative analyses and plays an important role in cancer migration and invasion (Wang et al 2018;Guo et al 2019;Li et al 2019).…”
Section: Discussionmentioning
confidence: 94%
“…YES1 amplification has been found in 15% of lung adenocarcinoma and 25% of lung squamous cell carcinoma patients, and YES1 expression was reported to be related to a shorter OS in NSCLC patients 22 . Garmendia et al 23 . demonstrated that YES1 amplification induces tumor growth as an oncogenic driver alteration in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Few cases of primary resistance to afatinib for patients harboring EGFR exon 21 L858R missense mutation have been reported and here we present the first case with concurrent alterations of EGFR exon 21 L858R missense mutation and YES1 amplification. Garmendia et al 23 . demonstrated that YES1 amplification presented a high sensitivity to dasatinib, an SFK inhibitor.…”
Section: Discussionmentioning
confidence: 99%